Pengaruh Lingkungan Teman Sebaya Terhadap Motivasi Belajar Matematika SiswaDevelopment Research, Teacher Competency, Research, Modified Model - Elinggrawati Elinggrawati; Tasnim Rahmat; Wedra Aprison; Haida Fitri (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is motivated by the results of observations where it is seen that the students' low motivation to learn mathematics is influenced by the peer environment. The formulation of the research problem is "Is there a significant influence of peer environment on students' motivation to learn mathematics in class XI SMA Negeri 4 Payakumbuh. The purpose of this study was to determine whether or not there was a significant influence of peer environment on students' mathematics learning motivation in class XI SMA Negeri 4 Payakumbuh. The hypothesis in this study is that there is a significant influence between the peer environment on students' mathematics learning motivation in class XI SMA Negeri 4 Payakumbuh in the academic year 2021/2022. This type of research is correlational. The nature of this research is ex post facto with quantitative methods. The population in this study were all students of class XI SMA Negeri 4 Payakumbuh as many as 8 classes totaling 290 students. The sample in this study was 35 students from all students in class XI SMA Negeri 4 Payakumbuh taken by random sampling, namely the technique of taking samples from the population randomly without regard to the strata in the population. The data collected is the result of filling out a peer environment questionnaire and students' motivation to learn mathematics by the respondents. From the results of data analysis shows the regression equation between the peer environment on students' mathematics learning motivation in class Y = 41.35965 + 0.424927 X with a correlation coefficient value of rxy = 0.603571936 which shows a very strong relationship and a determinant coefficient of KD = 36,4299%. The regression significance test was obtained by Zcount = 3.519398924 and Ztable = 1.96 or Zcount > Ztable. So it can be concluded that there is a significant influence of the peer environment on students' learning motivation in mathematics in class XI SMA Negeri 4 Payakumbuh in the 2021/2022 academic year.